SCREENING OF RICINUS COMMUNIS LINN. LEAVES FOR ANTICONVULSANT AND ANALGESIC ACTIVITY - Padma L. Ladda (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective- Maximal electroshock seizures (MES) in albino rats and pentylenetetrazole (PTZ) induced seizures in albino mice were used to study anticonvulsant activity of Ricinus communis Linn. leaves extract belonging to family Euphorbiaceae. Different extracts of Ricinus communis Linn. were also screened for analgesic activity by Eddy's hot plate method. Methods- The ethanolic leaves extract of Ricinus communis Linn. was administered orally as (250 mg/kg) in both the experimental models and the effects were compared with phenytoin in MES method and diazepam in PTZ induced seizures method as standard control respectively. The latency of seizures and % of mortality were observed. Result- The ethanolic leaves extract suppressed duration of tonic convulsions and showed recovery in maximal electroshock induced seizures. It also decreased number, duration of convulsions, delayed time of onset of clonic convulsions and showed mortality protection significantly in pentylenetetrazole induced seizures. The ethanolic extract delayed the occurrence of MES and PTZ convulsions, exerts their anticonvulsant effect.Conclusion-This study confirmed the oral analgesic and anticonvulsant properties of mature fresh leaves of Ricinus communis Linn. claimed in the Ayurveda medicine and do have pain suppressing activities possibly mediated via PG synthesis inhibition, membrane stabilizing. The extract could have exhibited the activity by interfering with GABA, glutamate mechanisms. Phytochemical investigation reveals the presence of flavonoids, fatty acids attributed to their anti-convulsant action. Future study should focus on isolation of these components for the observed analgesic, anticonvulsant action and identification of its mechanism of action.Key Words: Ricinus communis Linn., anti-convulsant, analgesic, MES, Pentylenetetrazole